(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
On the present scenario, online shopping is one of the preferred modes of shopping among the people who are in the practice of using mobile phones and personal computers. This scenario has changed in just a span of 10 or 15 years and a number of factors are responsible for the same like spread of education in the country, mobile technology made easy and even the cost of using the same has been brought down. From the rural parts of the country to the metro cities most of the people are somehow connected to the drive of online shopping. This present study is focused on how the easy availability of internet and use of mobile devices has changed the face of shopping concerns of the customers and also identify the reasons for which the customers are finding online shopping more convenient.Jaipur the capital city of Rajasthan, India is considered for the study and 200 carefully selected respondents were contacted. The data is collected with the help of a scale based questionnaire and data is analyzed by using SPSS ver. 23.0.